SF-36 and the malay translated audit of dependaent diabetes quality of life (ADDQOL) performances among type 2 diabetes patients - M Kamarul Imran MD,; AI Aziz Phd,; L Naing MPH,; W.B. Wan Mohamad FRCP, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
A cross sectional study was done to examine the performance of SF-36 and the Malay translated Audit of Dependent Diabetes Quality of Life (ADDQOL). Univariate analysis showed there was no significant difference in the ADDQOL scores. Ancova showed that Vitality score and Bodily Pain score was different in some areas. Only Mental Health scales were different between sexes among all scales in SF-36.The Malay translated ADDQOL and most of SF-36 performances were mostly not affected by different gender, types of treatments, glycemic controls and presence of complications.